Aging in 18650-type Li-ion cells examined with neutron diffraction, electrochemical analysis and physico-chemical modeling. (June 2018) - Paul, Neelima; Keil, Jonas; Kindermann, Frank M.; Schebesta, Sebastian; Dolotko, Oleksandr; Mühlbauer, Martin J.; Kraft, Ludwig; Erhard, Simon V.; Jossen, Andreas; Gilles, Ralph
Highlights: Aging in NMC/C cells compared by neutron diffraction and electrochemical analysis. A physico-chemical aging model is developed and validated for aging contributions. Capacity loss is mainly due to loss of cyclable lithium into SEI layer growth. Model and neutron data agree on cathode stoichiometry shift of 0.08. Model and neutron data agree on anode stoichiometry shift of about 0.19. Abstract: Aging in NMC/C cells (NMC-Li y (Ni0.33 Mn0.33 Co0.33 )O2 ), cycled 1000 times at a 1 C rate, has been characterized by in situ neutron diffraction and electrochemical analysis. These experimental results have been validated by a physico-chemical aging model, which attributes capacity fade to growth of a continuous SEI film on the anode. Neutron diffraction of the cells indicate a cyclable lithium loss corresponding to a capacity fade of about 23% in both electrodes of the cycled cell. The cycled cell suffers an anode stoichiometry shift from x  = 0.84 to x  = 0.65 in Li x C6 (0 ⩽  x  ⩽ 1) in its fully charged state and a cathode stoichiometry shift from y  = 0.89 to y  = 0.81 in Li y (Ni0.33 Mn0.33 Co0.33 )O2 (0 <  y  ⩽ 1.05) in its fully discharged state. Anode ( x  = 0) as well as cathode stoichiometries ( y  = 0.54) remain practically unchanged in the cell's fully discharged and charged states, respectively. These stoichiometry shifts match well with those derived from the model, and both neutron diffraction and model are in good agreement to the electrically determined capacity fade of 21%. In fact, cyclable lithium losses slightly exceed this value. Thus, capacity fade in these cells is mainly due to loss of cyclable lithium into the continuous growth of a SEI film on the anode surface.